(untitled) (Agricultural Engineering, 2019)
The paper presents kinetics of osmotic dehydration of plums in relation to the treatment time and concentration of sucrose solution. The main aim of the study was polyoptimisation of the preservation process, namely selection of optimal parameters of osmotic dehydration processes including changes in selected quality indicators. Defining of optimal conditions of the entire course of preservation may influence limitation of consumption of preserving substances (osmotic substances) and reduction of the energy demand. Based on the research which was carried out, it was found that parameters of osmotic dehydration had a significant impact on mass transfer coefficients and physico-chemical indicators of fruit - along with the increase of concentration of osmotic solution and extension of the time of the process, the increase of the investigated sizes was observed. In the second part of the paper, optimization of the fruit preservation process was performed. The idea of the objective function consisted in minimization of the difference between the expected values of criteria and the values obtained from the experimental results. For the defined scalar optimization criterion an explicit relation between quality and cost of the product was showed.